Pre-clinical characterization of Dacomitinib (PF-00299804), an irreversible pan-ErbB inhibitor, combined with ionizing radiation for head and neck squamous cell carcinoma. - Justin P Williams (PLoS ONE, 2014)
Epidermal growth factor receptor (EGFR) is over-expressed in nearly all cases of squamous cell carcinoma of the head and neck (SCCHN), and is an important driver of disease progression. EGFR targeted therapies have demonstrated clinical benefit for SCCHN treatment. In this report, we investigated the pre-clinical efficacy of Dacomitinib (PF-00299804), an irreversible pan-ErbB inhibitor, both alone and in combination with ionizing radiation (IR), a primary curative modality for SCCHN. One normal oral epithelial (NOE) and three SCCHN (FaDu, UT-SCC-8, UT-SCC-42a) cell lines were used to conduct cell viability, clonogenic survival, cell cycle, and immunoblotting assays in vitro, using increasing doses of Dacomitinib (10-500 nM), both with and without IR (2-4 Gy). The FaDu xenograft model was utilized for tumor growth delay assays in vivo, and immunohistochemical analyses were conducted on extracted tumors. A dose-dependent reduction in cell viability and clonogenic survival after Dacomitinib treatment was observed in all three SCCHN models. Treatment led to a significant reduction in EGFR signalling, with a subsequent decrease in phosphorylation of downstream targets such as ERK, AKT, and mTOR. In vivo, Dacomitinib treatment delayed tumor growth, while decreasing phospho-EGFR and Ki-67 immunoexpression. These effects were further enhanced when combined with IR, both in vitro and in vivo. The preclinical data support the further evaluations of Dacomitinib combined with IR for the future management of patients with SCCHN.